I need answer this whit steps.
pls.
Step-by-step explanation:
6+3((4-2(4-7))
1. 6+3((2(4-7))
2. 6+3((2(*-3)
3. 6+3(-6)
4. 6+(3*-6)
5. 6+-18
6. -12
Answer: a=4, b=16, c=12
Step-by-step explanation:
Use the intercept form: a(x - p)(x - q) where p & q are the intercepts.
Given: p = -3, q = -1, and y-intercept (c) = 12
a[x - (-3)][x - (-1)]
= a(x + 3)(x + 1)
= a(x² + 4x + 3)
= ax² + 4ax + 3a
y-intercept = 12
3a = 12
a = 4
Substitute a = 4
4x² + 4(4)x + 3(4)
= 4x² + 16x + 12
I need to calculate the derivative of this function but it will be difficult without even knowing what the 2 means lol.
Thnx in advance
It means you have to multiply log(x) by itself.